UMKM SOCIALISATION: CONCRETE STEPS FOR VILLAGE COMMUNITY SERVICE - Sitti Nur Alam; Sri Mulyono; Widjanarko (Adiba Aisha Amira, 2024)
The MSME socialisation programme in the village aims to introduce and develop small businesses in the rural environment. This activity is conducted to improve the village economy by providing villagers with basic knowledge and skills about Micro, Small and Medium Enterprises. In this programme, villagers are given materials on the basics of MSMEs, how to start a business, and simple marketing strategies. In addition to theory, participants are also invited to practice directly, such as making a business plan and learning how to promote a business that is suitable for small businesses in the village. The implementation of the programme involved collaboration between universities, local entrepreneurs, and the local government. This was done so that participants could gain many perspectives and real-life experiences. The results of the programme can be seen from the increased interest of villagers to start a business, the emergence of various new business ideas, and the increase in economic activities in the village. It is hoped that this MSME socialisation can provide long-term benefits for the economic development of the village.